An overview of brain-like computing: Architecture, applications, and future trends - Ou, Wei; Xiao, Shitao; Zhu, Chengyu; Han, Wenbao; Zhang, Qionglu (Frontiers in Neurorobotics, 2022)
With the development of technology, Moore's law will come to an end, scientists try to find a new way out in brain-like computing. But we still know very little about how the brain works. At the present stage of research, brain-like models are all structured to mimic the brain in order to achieve some of the brain's functions, and then continue to improve the theories and models. This paper summarizes the important progress and status of brain-like computing, summarizes the generally accepted and feasible brain-like computing models, introduces, analyzes and compares the more mature brain-like computing chips, outlines the attempts and challenges of brain-like computing applications at this stage, and looks forward to the future development of brain-like computing. It is hoped that the summarized results will help relevant researchers and practitioners to quickly grasp the research progress in the field of brain-like computing and acquire the application methods and related knowledge in this field.